2023
DOI: 10.33233/rbfex.v22i1.5470
|View full text |Cite
|
Sign up to set email alerts
|

Reprodutibilidade de medidas do controle inibitório, memória de trabalho e flexibilidade cognitiva em mulheres idosas

Abstract: Introdução: A Função Executiva é expressa nas atividades do dia a dia por meio do controle inibitório, memória de trabalho e da flexibilidade cognitiva. Apesar da importância de avaliar essas medidas, existem divergências sobre a reprodutibilidade dos testes. Objetivo: Testar a reprodutibilidade do Stroop Color-Word Test, Teste dos Cubos de Corsi e Teste de Trilhas em mulheres idosas. Métodos: Trinta e cinco mulheres idosas realizaram o Stroop Color-Word Test (Controle Inibitório), Teste dos Cubos de Corsi (Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The composite score calculated by multiplying the sequencing (i.e., the number of levels achieved) by the number of correct responses was used to measure working memory. This score demonstrated an intraclass correlation coefficient greater than 0.80 for older people [39,40].…”
Section: Memory Workingmentioning
confidence: 90%
See 2 more Smart Citations
“…The composite score calculated by multiplying the sequencing (i.e., the number of levels achieved) by the number of correct responses was used to measure working memory. This score demonstrated an intraclass correlation coefficient greater than 0.80 for older people [39,40].…”
Section: Memory Workingmentioning
confidence: 90%
“…These trials consisted of 60 congruent words (where the word's meaning matched the ink color) and 60 incongruent words (where the word's meaning and ink color diverged). The variables analyzed in the study were response time for congruent and incongruent trials, which showed good reliability for older women with an intraclass correlation coefficient of 0.92 and 0.91, respectively [39,40].…”
Section: Executive Function Inhibitory Controlmentioning
confidence: 99%
See 1 more Smart Citation